2014
DOI: 10.1080/11356405.2014.973670
|View full text |Cite
|
Sign up to set email alerts
|

A synthesis of research on effectiveness of school-based drug prevention programmes / Claves de eficacia de los programas de prevención de consumo de sustancias en el contexto escolar: una meta-revisión

Abstract: Resumen:Pese a que disponemos de información relevante sobre qué aspectos se relacionan con la eficacia de los programas de prevención de drogadicciones en el ámbito escolar, existen aún datos contradictorios que hacen necesario continuar arrojando luz sobre esta cuestión. En esta investigación se trató de determinar cuáles eran las variables que, según los estudios de revisión, fomentan la eficacia de estos programas y qué peso tiene su evidencia empírica; además se examinaron algunas características de los d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(14 citation statements)
references
References 37 publications
0
14
0
Order By: Relevance
“…Those skills are generically called life skills, already recognized as the "primary focus" of school-based prevention (Winters et al 2007, p. 375). This primacy was reported in a systematic review of 17 recent studies, published by Jiménez et al (2014), that identified 29 elements associated with the effectiveness of prevention at school, highlighting the training of life skills.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Those skills are generically called life skills, already recognized as the "primary focus" of school-based prevention (Winters et al 2007, p. 375). This primacy was reported in a systematic review of 17 recent studies, published by Jiménez et al (2014), that identified 29 elements associated with the effectiveness of prevention at school, highlighting the training of life skills.…”
Section: Introductionmentioning
confidence: 99%
“…Each reference on the right column clearly cites the element on the left column as element of effectiveness of school-based prevention of drug use. Ramos et al (2010) and Jiménez et al (2014) cited most of them as key of effectiveness. According to Jiménez et al, the elements were ranked by the strengthof-evidence in their effectiveness, indicating the weight of the evidence observed for each of them.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations